8x+12=26+x

Simple and best practice solution for 8x+12=26+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x+12=26+x equation:


Simplifying
8x + 12 = 26 + x

Reorder the terms:
12 + 8x = 26 + x

Solving
12 + 8x = 26 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
12 + 8x + -1x = 26 + x + -1x

Combine like terms: 8x + -1x = 7x
12 + 7x = 26 + x + -1x

Combine like terms: x + -1x = 0
12 + 7x = 26 + 0
12 + 7x = 26

Add '-12' to each side of the equation.
12 + -12 + 7x = 26 + -12

Combine like terms: 12 + -12 = 0
0 + 7x = 26 + -12
7x = 26 + -12

Combine like terms: 26 + -12 = 14
7x = 14

Divide each side by '7'.
x = 2

Simplifying
x = 2

See similar equations:

| 2ab-b+6ba= | | 5(f-6)=15 | | x/5-1=x/2 | | 5t-18=-4 | | 10(s-3)=-122 | | 4s=4 | | 2ln(4x-1)=8 | | 7-5/6X9 | | (9X)+2=8x | | 8(3s+5)=184 | | 8(2l+10)=128 | | 7x+2y=39 | | 15x-18-3x=16 | | -5(5N+1)=30 | | 4z/9-8=-2 | | 5x*5x+5x=0 | | (27x)^(1/3) | | 5x-6y=-15 | | x/8-9=1 | | 5x+(x+6)=-39-3x | | V^2-8v=-15 | | z/9-7=1 | | (3n^(1/2))^-6 | | 2(y+4)(y+4)=22 | | -12m^2-4m-5-19m^2-13m= | | 3(x+5)=21+4 | | 6y7/3y4 | | X^2+7-98=0 | | 3x-1=3x+3 | | T^2+7-98=0 | | =970 | | x^2-9x+24=2x |

Equations solver categories